Through an Anglo-Irish Lens: The Dublin University Magazine’s (1833-1877) Perception of Hungary - Zarka, Zsuzsanna (FOCUS: Papers in English Literary and Cultural Studies, 2008)
The Irish publication market in the first three decades of the nineteenth century was dominated by political periodicals. The 1830s introduced and popularized the genre of literary and political magazines, opening up the possibility to reach and recruit a larger circle of readership (Hayley and McKay 29-33). Out of the wide spectrum of potential approaches, the Protestant The Dublin University Magazine (DUM), which was published from 1833 to 1877 under this name, seemed outstanding for several reasons. Although originally modelled on and seeking to compete with the standards of distinctive English periodicals like Blackwood’s and Fraser’s Magazine (Houghton 4: 193), DUM also aimed to endow their new periodical with a characteristic Irish voice from the onset. This manifested itself in the Protestant character of the political affiliations of the compilers, implying a specialized Irish point of view. The present article is intending to shed light on this particular attitude by examining the periodical through the lens of their commentaries on the Austro-Hungarian Empire, more specifically Hungary, as an entity. Although the analysis will discuss only those articles that provided readers with information on the contemporary political situation of the kingdom, it will mention examples too which introduced some features of Hungarian culture and literature. By focusing on the questions the articles raised, it is hoped to gain an insight into the magazine’s perspective on and perception of a region of Europe which, one may presume, had entirely escaped the Protestant readerships’ attention or interest.